The effect of three different acrylic intraocular lenses on the glistening formation - Todorović, Dušan; Srećković, Sunčica; Petrović, Nenad; Resan, Mirko; Damjanović, Goran; Todorović, Željko; Šarenac Vulović, Tatjana (Vojnosanitetski pregled, 2025)
Background/Aim. One of the postoperative complications of phacoemulsification is the formation of fluid-filled microvacuoles inside the implanted intraocular lens (IOL). This condition is known as ‘glistening’. The aim of this study was to determine the incidence of glistening formation after the implantation of three different acrylic IOLs during the two-year follow-up period. Methods. Cataract surgery was performed in 93 patients (93 eyes) with developed senile cataracts. According to the implanted IOL, patients were equally divided into three groups: group with single-piece hydrophilic (SPHphil) acrylic IOL, group with single-piece hydrophobic (SPHphob) acrylic IOL, and group with three-piece hydrophobic (TPHphob) acrylic IOL. The presence of glistening was measured five times: 1, 6, 12, 18, and 24 months after phacoemulsification. Results. Statistically significantly lower glistening incidence was recorded in the SPHphil group compared to the SPHphob and TPHphob group, six months after phacoemulsification (p  0.05). Conclusion. The presence of glistening was recorded in all groups. Our results strongly suggest that the progression of glistening was the most pronounced in the first postoperative year. However, a very low glistening incidence associated with SPHphil IOL could be particularly beneficial in patients expected to develop increased postoperative inflammation.
Keywords: cataract; lenses, intraocular; ophthalmologic surgical procedures; phacoemulsification.